Growth Phases and Survival of High-system International New Ventures originating from Finland - Stotzka, Julia (My University, 2010)
The main objective of this research was to identify how rapidly internationalizing firms namely International New Ventures (INVs) can grow and survive to become strong organizations. Thus the growth phases of INVs were researched next to the critical points which need to be mastered throughout existence. Hereby the commercialization of business was observed as one particular challenge. The study put particular emphasis to investigate the external and internal factors influencing INV growth and survival. The theoretical part was based on earlier research with growth and survival being regarded from various perspectives such as the life-cycle approach and the resourced-based view. Based on the literature, a theoretical framework was created which was then tested via a multiple case study of five Finnish INVs from the high-systems business. In the case studies it appeared that support can be found for most of the theoretical propositions. INVs evolve through four growth stages. During this evolution, they face several crises putting survival at stake. Further, various critical decision making points need to be mastered by the firms during evolution. The empirical observation indicated that positive industry conditions are needed for INVs to sustain. In addition, firm factors such as sufficient resources and capabilities are critical next to a high entrepreneurial orientation. Further, strong customer orientation is required for high-system INVs. Moreover, a focused commercialization approach utilizing opinion leaders helps INVs to bring their business to a broader range of customers thus to grow and to survive.
Keywords: Rapidly Internationalizing Firms; International New Ventures; Born Globals; Growth Phases; Survival; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|